การสังเคราะห์งานวิจัยปัจจัยที่ส่งผลต่อคุณภาพ นักเรียนอาชีวศึกษา : การวิเคราะห์อภิมาน - ผิวทอง, พิษณุ; ปั้นหุ่น, สมพงษ์; อนุศาสนนันท์, สุรีพร; วงษ์นาม, ไพรัตน์ (วารสาร ศึกษาศาสตร์ มมร; Vol 6 No 2 (2018): วารสารศึกษาศาสตร์ มมร ปีที่ 6 ฉบับที่ 2 (กรกฎาคม - ธันวาคม 2561), 2018)
การวิจัยในครั้งนี้ มีวัตถุประสงค์เพื่อศึกษาคุณลักษณะของงานวิจัยเกี่ยวกับคุณภาพนักเรียนอาชีวศึกษา และสังเคราะห์งานวิจัยเกี่ยวกับคุณภาพนักเรียนอาชีวศึกษาด้วยการวิเคราะห์อภิมาน  งานวิจัยที่นำมาสังเคราะห์เป็นงานวิจัยที่ศึกษาเกี่ยวกับการพัฒนาคุณภาพของนักศึกษาอาชีวศึกษาที่ตีพิมพ์ระหว่างปี พ.ศ. 2540 -2558 จากมหาวิทยาลัย 23 แห่ง จำนวน 95 เล่ม ผลการวิจัยประกอบด้วยค่าดัชนีมาตรฐาน จำนวน 450 ค่า มีความแตกต่างกันตามคุณลักษณะของงานวิจัย ดัชนีมาตรฐานคุณภาพนักเรียนอาชีวศึกษามีแนวโน้มสูงขึ้นตามจำนวนหน้าหมดของงานวิจัย ช่วงเวลาที่ทำวิจัย สถาบันและสาขาวิชาที่ผลิตงานวิจัย สถานศึกษาที่เป็นพื้นที่วิจัย การตั้งสมมติฐานแบบมีทิศทาง ลักษณะของครอบครัวและคะแนนคุณภาพงานวิจัยที่สูง และเมื่อวิเคราะห์โดยพิจารณาคุณลักษณะของงานวิจัยเป็น 2 ระดับ พบว่า ระดับภายในเล่มวิจัยได้แก่ คะแนนรวมประเมินคุณภาพงานวิจัย ตัวแปรดัมมี่งานวิจัยที่หาความเที่ยงของเครื่องมือด้วยวิธีแอลฟา และลักษณะของนักเรียน  ส่วนในระดับเล่มวิจัย ได้แก่ การออกแบบการวิจัยเชิงทดลอง จำนวนหน้ารวมภาคผนวก และจำนวนสมมติฐาน This research aimed to study the research characteristics of factors influencing the performance of  students in vocational education and to synthesize the research findings through meta-analysis. The samples of the synthesis were 95 primary studies related to the effects of factors on the students’ performance published durings 1997 – 2015 from 23 universities. The reserch outcomes composed of 450 standard indices (adjusted correlation coefficient). Quantitative data were analyzed using meta-analysis; descriptive, crosstabulation, ANOVA, heirachical stepwise multiple regression and  Heirachical linear Model.             The research findings revealed that almost researches included were an experimental studies which conducted as the thesis titles for graduation in master degree. Indepenent variables of these study were teaching methods, students charateristics and family characteristics. Most students were drawn from Technical College majoring in Industrial Machinery Machanics. The Curriculum and Instruction Sciences was the main area has conducted the reseaches on the vocational student’s performances at the faculty of education in 23 universities. The standard indices of the synthesis are correlation coefficient adjusted for bias through Hedges’s J factor. All means of standard indidices of student performances were statitically difference among the research characteristic. The multiple regression coefficients showed that the standard indices of research on student performances increase through all pages of reserach, year, university, faculty department, research sites, set directional hypothesis, family characteristics, and quality scores of primary researchs. For multilevel analysis displayed highly effects of mean score of research quality, Cronbach’ alpha coefficient used, and student characteristics on the effect size in within unit. For between umit, the experimental research design, all pages of researhs, and number of hypothesis  explained all variance of effect size with statistical significantly.